Marjoram phytomass at harvest intervals in summer and winter transplants - Souza, Jéssica Maronez de; Cargnelutti Filho, Alberto; Silveira, Daniela Lixinski; Uliana, Daniela Barbieri; Loregian, Marcos Vinícius; Dumke, Gabriel Elias; Weschenfelder, Marlon Adonai Gregory (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to determine the harvest interval for phytomass production of marjoram (Origanum majorana) in summer and winter transplants. Two independent experiments were performed in off-ground cultivation: one with a summer and another with a winter transplant, in a completely randomized design with five harvest intervals (30, 45, 60, 72, and 90 days) and four replicates. The fresh and dry masses of leaves, branches, and aerial part were determined. For each plant, the production accumulated in the harvests was calculated as affected by days after the transplant. The fresh matter mass of the leaves was higher at the intervals of 60 and 90 days, in the summer transplant, and of 72 and 90 days, in the winter transplant. Harvesting at intervals of 60 days in the summer transplant and of 72 days in the winter transplant are appropriate for marjoram phytomass production.